2022
DOI: 10.3389/fmars.2022.1046808
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding reveals the differential sensitivity of planktonic microbiome to environmental filtering and biointeraction in Sansha Yongle blue hole

Abstract: The Sansha Yongle blue hole (SYBH) is the world’s deepest blue hole known so far and its unique hydrochemical characteristics make it a valuable site for studying biodiversity and ecological processes. Here, we used metabarcoding approach to investigate the diversity, assembly mechanism and co-occurrence pattern of planktonic microbiome in SYBH. Our results revealed the distinct separation of communities from upper oxic, middle oxic and suboxic-anoxic layer and significant day-night difference was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…The NCM proposed by Sloan et al 33 is particularly useful in quantifying the importance of neutral processes and has been employed in bacterial community 34 36 , eukaryotic community 37 and microeukaryotic community 38 , 39 . Although stochastic processes seem to influence planktonic microeukaryotes and deterministic processes dominate in prokaryotic plankton in the SYBH 10 , our data from SYBH sediments indicate that stochastic processes appear to shape the sediment communities. Our results show that stochastic processes contributed to ~ 55% of the variations in archaeal, bacterial, and eukaryotic communities in SYBH sediments (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The NCM proposed by Sloan et al 33 is particularly useful in quantifying the importance of neutral processes and has been employed in bacterial community 34 36 , eukaryotic community 37 and microeukaryotic community 38 , 39 . Although stochastic processes seem to influence planktonic microeukaryotes and deterministic processes dominate in prokaryotic plankton in the SYBH 10 , our data from SYBH sediments indicate that stochastic processes appear to shape the sediment communities. Our results show that stochastic processes contributed to ~ 55% of the variations in archaeal, bacterial, and eukaryotic communities in SYBH sediments (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Members of Thaumarchaeota, Arthropoda and Annelida also showed a high proportion of intra-phylum interactions. Chen et al 10 suggested that abiotic factors played a minor role in shaping microeukaryotic plankton community in SYBH, and interspecies cooperation might be one of the ecological strategies. Here, co-occurrence networks suggest that biotic interactions (e.g., mutualism, commensalism, synergism) may play an important role in the distribution of these dominant taxa of prokaryotic and eukaryotic communities in SYBH sediments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations